(untitled) (Journal of the College of Basic Education, 2023)
Used in this study to prepare for the new cross linked polymer adsorption to remove heavy metals(Hg*’,Cd*’,Zn*?,Pb”) in aqueous solution . Using UV-Visible spectrophotometer technique to determine the amount of adsorption and factors affecting the adsorption of PH and the distribution coefficient and the effect of temperature and study the thermodynamic functions process. The results showed that the highest amount of adsorption was ion (Zn*), which was 98.9% , Pb**= 80.2% ,Cd=75.3% and Hg*=67.9%. The results the thermodynamic parameter showed that reaction exothermic and value of AG is spontaneous. The adsorption kinetic was found to follow pseudo-second order rate model, due to the high correlation coefficient(R’) and agreement between the experimental and calculated value of qe (mg/l). The results proved the applicability of isotherm Freundilch equation for adsorption coefficient higher than for Langmuir correlation equation.